Impact of environmental, social, and governance activities on the financial performance of Indian health care sector firms: Using competition as a moderator - Bhakti Agarwal; Rahul Singh Gautam; Pooja Jain; Shailesh Rastogi; Venkata Mrudula Bhimavarapu; Saumya Singh (Journal of Risk and Financial Management, 2023)
Environmental, social, and governance (ESG) activities have become essential and viable activities of corporations because of the increase in concern for environmental, social, and governance issues. The motive of this research is to measure the effect of ESG on the financial performance (FP) of healthcare corporations using the market-to-book value (MTB) ratio as a proxy of FP. A sample of 33 pharma companies in India from 2011 to 2020 has been considered. The study relies on the panel data method to assess the association between ESG and FP. The potential moderating role of competition has also been studied to simplify their relationship in this framework. The finding of this study is that there is a significant negative association between ESG and FP, and it is also found that when competition is used as a moderator, it results in a significantly positive impact on the ESG and FP of healthcare companies. This study increases the understanding of the association between ESG and FP and helps corporations to formulate corporate strategies and stakeholders to make investment decisions. The originality of this study is that it addresses the impact of competition on ESG and FP of the healthcare industry and will become foundational literature for future studies.
Keywords: 650; competition; corporate governance; ESG; financial performance; healthcare